Towards additive manufacturing of dielectric accelerating structures. (July 2020) - Kellermeier, Max; Zinsli, Simon; Dorda, Ulrich; Ischebeck, Rasmus; Lehmann, Jonas; Hermann, Benedikt; Flöttmann, Klaus; Lemery, François; Dinter, Hannes; Lombosi, Csaba; Magjar, Marijo; Stingelin, Lukas; et al.
Abstract: Additive manufacturing techniques such as stereolithography have developed rapidly in the last decade and provide the ability to simplify prototyping and manufacturing of unique, complex structures. For the application to dielectric accelerating structures a precise knowledge of the dielectric permittivity of the material is essential to the design. Here we present the characterization of commercially available polymers used in stereolithographic manufacturing by means of refractive index and absorption in the frequency range from 220 GHz to 330 GHz, and around 60 GHz. Vacuum compatibility has been tested with respect to achievable pressure level and residual gas mass spectra. In the future the polymer properties will be applied to designs of accelerating structures as well as couplers for terahertz-driven dielectric accelerator components.